2020
DOI: 10.1039/d0sc01290d
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational characterization of a diiron bridging hydride complex – a model for hydrogen catalysis

Abstract: Fe–H–Fe bridging iron hydrides in model systems and metalloenzymes: benefits and challenges in revealing their vibrational signatures using NRVS spectroscopy and DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…People need 36-48 h to move in and set up the HRM and other instruments at the beginning of each beamtime [8]. Nevertheless, researchers are rewarded with amazing NRVS results [7,8,45,47,[65][66][67][68][69].…”
Section: High-resolution Monochromatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…People need 36-48 h to move in and set up the HRM and other instruments at the beginning of each beamtime [8]. Nevertheless, researchers are rewarded with amazing NRVS results [7,8,45,47,[65][66][67][68][69].…”
Section: High-resolution Monochromatorsmentioning
confidence: 99%
“…A rough recommendation is that NMA should be utilized for smaller/high-symmetry systems where the size of the parameter space can be reasonable and group theory insights are useful. However, in recent years, DFT calculations have been popular as a straightforward approach to interpret vibrational spectra including NRVS [ 7 , 14 , 30 , 32 , 36 , 38 , 44 , 66 , 68 ].…”
Section: Experimental Aspects (Iii): Data Processmentioning
confidence: 99%
“…Nuclear resonance vibrational spectroscopy (NRVS) 13−16 has become a popular technique for elucidating the elementselective normal modes of appropriate Mossbauer isotopes. 13−18 In previous work, we have shown that 57 Fe-NRVS can be utilized to observe Fe−H bending and Fe−H−Fe(Ni) wagging modes in various model compounds 19 as well as intermediate species of [NiFe] 20 and [FeFe] hydrogenases. 21−23 However, to date, the only reported Fe−H stretching modes were the bands around 1230/1430 cm −1 for a doubly bridging Fe(μ-H) 2 Fe complex 24 and at 1468/1532 cm −1 for a singly bridging Ni(μ-H)Fe complex.…”
mentioning
confidence: 99%
“…Nuclear resonance vibrational spectroscopy (NRVS) has become a popular technique for elucidating the element-selective normal modes of appropriate Mössbauer isotopes. In previous work, we have shown that 57 Fe-NRVS can be utilized to observe Fe–H bending and Fe–H–Fe­(Ni) wagging modes in various model compounds as well as intermediate species of [NiFe] and [FeFe] hydrogenases. However, to date, the only reported Fe–H stretching modes were the bands around 1230/1430 cm –1 for a doubly bridging Fe­(μ-H) 2 Fe complex and at 1468/1532 cm –1 for a singly bridging Ni­(μ-H)Fe complex . To better gauge the feasibility for observing even higher frequency stretching modes expected for an iron-terminal hydride and dihydrogen, we have applied NRVS to examine a well-studied trans -[ 57 Fe­(η 2 -H 2 )­(H)­(dppe) 2 ]­[BPh 4 ] [dppe = 1,2-bis­(diphenylphosphino)­ethane] complex, , hereafter called 1 H H2 .…”
mentioning
confidence: 99%
“…NRVS is a unique technique using high intensity X-ray, produced by synchrotron radiation, to investigate the atomic vibration in molecules. Vibration modes of a specific atom, selectively excited via the nuclear level, give quite different and complementary information from that taken by Raman or infrared (IR) spectroscopy in the examination of the active center of metalloenzyme (Figure 4) [8][9][10][11][12]. X-rays from the synchrotron radiation can be also utilized for light source of new imaging systems that visualize biometal distribution and chemical status in tissues or even in cells.…”
mentioning
confidence: 99%